Non-Pharmaceutical Interventions Implemented to Control the COVID-19 Were Associated With Reduction of Influenza Incidence - Huang, Qing-Mei; Song, Wei-Qi; Liang, Fen; Ye, Bi-Li; Li, Zhi-Hao; Zhang, Xi-Ru; Zhong, Wen-Fang; Zhang, Pei-Dong; Liu, Dan; Shen, Dong; Chen, Pei-Liang; Liu, Qu; et al. (Frontiers in Public Health, 2022)
Background: Nonpharmaceutical interventions were implemented in most countries to reduce the transmission of COVID-19. We aimed to describe the incidence of influenza in four countries in the 2019-2020 season and examined the effect of these nonpharmaceutical interventions on the incidence of influenza. Methods: We used the network surveillance data from 2015 to 2020 to estimate the percentage increase in influenza cases to explore the effect of nonpharmaceutical interventions implemented to control the COVID-19 on the incidence of influenza in China, the United States, Japan, and Singapore. Results: We found that the incidence of influenza has been almost zero and reached a persistent near-zero level for a continuous period of six months since epidemiologic week 14 of 2020 in the four countries. Influenza incidence decreased by 77.71% and 60.50% in the early days of COVID-19 in the 2019-2020 season compared to the same period in preceding years in Japan and Singapore, respectively. Furthermore, influenza incidence decreased by 60.50%–99.48% during the period of compulsory interventions in the 2019-2020 season compared to the same period in preceding years in the four countries. Conclusion: These findings suggest that the application of nonpharmaceutical interventions, even everyday preventive action, was associated with a reduction of influenza incidence, which highlights that more traditional public health interventions need to be reasserted and universalized to reduce influenza incidence.